Law enforcement over illegal fishing to protect coral reefs during the Covid-19 pandemic in Buton - Dewi, Indah Kusuma; Hardin, Hardin; Asdin, Asdin (Faculty of Law, University of Muhammadiyah Malang, 2022)
The purpose of this study was to determine the role and obstacles faced by Fishery Civil Servant Investigators (FCSI) in the prevention and handling of Fisheries Crimes in the Buton Regency. With empirical legal methods, research data were obtained from direct interviews, showing that in 2018 there were two cases of destructive fishing using the fish bombing method, three cases in 2019, namely one case of fish bombing and two cases of exploitation of protected marine habitats, while in 2020 and 2021, there were two cases of fish bombing each. The results showed that Fisheries FCSI’s role constitutes prevention and prosecution for fisheries crime involving the destruction of ships that do not have permits for fishing vessels with sizes above 5 GT, exploitation of protected fish habitats, and fishing vessels failing to demonstrate proper seaworthiness. Fisheries crime cases that occur are fishing practices that involve the destruction of fish resources and aquatic habitats such as fish bombing, fish anesthesia, and the use of cyanide poison. Law enforcement during the covid-19 pandemic over these cases is carried out online at the witness examination stage or at a stage that involves the investigation of the suspect through a video conference interview. Provided that there is a Summoning Letter, based on Article 112 of the Criminal Procedure Code, the obstacles experienced by the Fisheries FCSI are influenced by internal factors in the form of lack of quality and quantity of supervision facilities and infrastructure, human resources, budget, and poor handling of evidence. Meanwhile, external factors involve the lack of public awareness to prevent the occurrence of fisheries crime, the lack of supporting facilities and infrastructure for the Supervisory Community Group, and weak coordination between law enforcement institutions.